Relationship between white matter pathology and performance on the General Movement Assessment and the Test of Infant Motor Performance in very preterm infants. (April 2016) - Peyton, Colleen; Yang, Edward; Kocherginsky, Masha; Adde, Lars; Fjørtoft, Toril; Støen, Ragnhild; Bos, Arend F.; Einspieler, Christa; Schreiber, Michael D.; Msall, Michael E.
Abstract: Background: Cerebral Magnetic Resonance Imaging, the General Movement Assessment, and the Test of Infant Motor Performance are all tools that can predict neurodevelopmental outcome in preterm infants. However, how these tests relate to each other is unclear. Aims: To examine the relationship between cerebral Magnetic Resonance Imaging measured at term age, and the General Movement Assessment and Test of Infant Motor Performance measured at 10–15 weeks post-term age. Study design: Prospectively collected data in a sample of very preterm infants. Subjects: Fifty-three infants (23 female, 30 male) with a median gestational age of 28 weeks (range: 23–30 weeks) and a median birth weight of 1000 g (range: 515–1465 g). Outcome measures: Test of Infant Motor Performance, General Movement Assessment. Results: Infants with abnormal white matter were significantly more likely to have both abnormal general movements (p = 0.01) and abnormal Test of Infant Motor Performance scores (p = 0.001). Infants with abnormal general movements were significantly more likely to have lower Test of Infant Motor Performance Scores (p = 0.01). Conclusions: Abnormal white matter is related to motor deviations as measured by the General Movement Assessment and the Test of Infant Motor Performance as early as 3 months post-term age in a cohort of preterm infants. Highlights: Preterm infants with abnormal white matter were more likely to have both abnormal general movements and Test of Infant Motor Performance Scores. Preterm infants with abnormal general movements at 10–15 weeks post-term age were more likely to have abnormal TIMP scores at the same age. Qualitative MRI scoring detected white, but not gray matter abnormalities in a cohort of preterm, very-low birth weight infants at term-age.